Reliability Assessment of Steel Plane Frame’s Buckling Strength Considering Semi-rigid Connections - Tran, N. L.; Nguyen, T. H. (Engineering, Technology & Applied Science Research, 2020)
The buckling strength of a structure depends hugely on material properties, geometry dimensions, and boundary conditions that are potentially random. This paper presents an assessment of the safety of buckling strength of steel plane frame semi-rigid beam-column connections. The Newton-Raphson method is used to solve the nonlinear equation for the buckling limit of the column. The reliability of the structure is evaluated by the Monte Carlo simulation method. The effects of input parameters are also investigated.